Sharia and the Press in Nigeria: Islam versus Western Christian Civilization by Ibrahim Ado-Kurawa (Kano, Nigeria: Kurawa Holdings, 2000. 461 pages.) (American Journal of Islam and Society, 2002)
Over the decades, Nigerian political elites have devised various constitutionaland administrative arrangements to cope with the country's complexethnic and religious pluralism. Yet, peace and stability have been elusive,as the country continues to experience severe religious and communal conflicts.These are reflected in the highly polemical book in which AdoKurawatries to trace the origin and nature of what he calls the hostility ofwestern Christian representatives towards Islam.In the book, Ado-Karuwa attempts to argue that the secular publicspace is too inflected with Christian values to make a claim to neutrality,and he uses Nigeria as a case study. He begins by noting that historically,Islam in Europe was tolerant and accommodative of the Christian religion,but this was not reciprocated when the Crusades were launched and"Muslims ... received the worst treatment imaginable." According to him,the failure of the armed campaign prompted Christian clerics to embark onan intellectual attack that entailed the negative representation of Islam inscholarly writings. What emerged, according to him, was a body of knowledgethat explained the superiority of the West over the Islamic world.Contemporary global dominance by the West has also opened the door foracademic institutions in Europe and America to strangulate Islam under theguise of promoting universal science.Ado-Karuwa relates the above to Nigeria by noting that, within thecountry, both Christian intellectuals and some British-trained Muslims actas agents of the West by promoting a secularism that marginalizes Islam.After a lengthy polemic about orientalism, colonialism, and Americanimperialism, the author returns to the issue of secularism, which he discussesgenerally without relating it concretely to Nigeria. He does not showhow secularism in Nigeria marginalizes Islam; neither does he make effortsto show that secularism is tainted by Christian doctrines, in the mannerdone by Louis Dumont. Instead, he undermines his project by arguing thatChristianity declined in Europe after secularism was enthroned by theReformation and the Renaissance, and that in Sweden attendance in theLutheran Church is only 5 percent. If it is true, as he argues, that the ...